PENGARUH FINANCIAL DISTRESS, PERENCANAAN PAJAK, UKURAN PERUSAHAAN, KOMITE AUDIT DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA - Khairunnisa, Jihan Muthi'ah; ., Majidah; ., Kurnia (2020)
This study aims to determine the effect of financial distress, tax planning, firm size, audit committe and audit quality on earning management on infrastructure, utilities and transportation company listed on Indonesia Stock Exchange (IDX) period 2015-2018. The method in this study used a quantitative method. The sample was determined using a purposive sampling method from 29 company samples. The statistical analysis used is data panel regression analysis. Simultaneously, the results indicates that financial distress, tax planning, firm size, audit committee and audit quality simultaneously have a significant influencen earning management. Meanwhile, partial analysis showed that financial distress, tax planning, firm size, audit quality have no effect on earning management, and the audit committee has negative effect on earning management.